Isolation of Normal Fibroblasts and Their Cancer-Associated Counterparts (CAFs) for Biomedical Research - Dvořánková, BarboraBarbora; Lacina, Lukáš; Smetana, Karel (Methods in molecular biology (Clifton, N.J.), 2019)
Cancer-associated fibroblasts (CAFs) represent a crucial component of cancer microenvironment. CAFs significantly influence biological properties of various types of cancer in terms of local aggressiveness, recurrence, and metastatic behaviour. This chapter summarizes a simple protocol for isolation of normal fibroblasts and their cancer-associated counterparts from normal human skin and mucosa, respectively, as well as from samples of human tumours such as basal/squamous carcinoma, melanoma, and breast cancer, and employment of this procedure for other types of cancer is possible. Isolated fibroblasts can be expanded in vitro and employed for further analysis of, e.g., DNA, RNA, protein, etc.
Keywords: Fibroblast; Cancer-Associated Fibroblasts; Cells, Cultured; lidé; Fibroblast isolation; fibroblasty; separace buněk; kultivované buňky; Humans; Cell Separation; Skin; Biomedical Research; Cancer-associated fibroblast; Cancer microenvironment; nádory; kůže; Cell cultivation; Fibroblasts; biomedicínský výzkum; fibroblasty asociované s nádorem; Neoplasms